Visualization of human brainstem substructures using gray matter nulling 3D-MPRAGE at 7 Tesla. Issue 3 (March 2016) - Daeubler, B.; Wyss, M.; Bruegger, M.; Vionnet, L.; Brunner, D.; Pruessmann, K.
Abstract : Background: The human brainstem is one of the most complex neural entities, in both, structural and functional domains. Its plurality of small and densely packed substructures results in demanding settings for in vivo MR visualization. We addressed this issue applying ultra-high field MRI at 7 Tesla focusing on enhanced differentiation of brainstem substructures. This approach is an essential prerequisite breaking down the complex brainstem anatomy. Methods: A modified 3D-MPRAGE-sequence in the sagittal and transverse plane was applied in a 7T MR-system. To compensate for B1-inhomogeneities, a highly adiabatic inversion prepulse was implemented. Five healthy volunteers were examined. The resulting images were visually correlated to histological plates and post-mortem MRI images from Duvernoy's Atlas. Results: We identified 22 structures (sagittal), clearly assignable to histology data. In the brainstem 12 substructures were manually outlined for all five subjects, also based on histology. Adopting histology nomenclature clearly identifiable structures were labeled. Conclusions: Optimized 3D-MPRAGE-imaging in the gray matter nulling regime at 7 Tesla provides enhanced image contrast between substructures in the human brainstem, giving rise to better understanding anatomy and potentially related pathology.